Clinical presentation and course of Type 1 diabetes: A Hospital based longitudinal study over a period of ten years - Karki, ST; Yadav, AK; Joshi, P; Karki, BB; Mall, D (Journal of Diabetes and Endocrinology Association of Nepal, 2025)
Background: Type 1 Diabetes Mellitus in children once considered a very rare disease is no rarer. Being chronic illness diabetes in early life increases the risk of morbidity thereby impairing physical, mental as well as social development. This retrospective study was planned to find the clinical picture, complications and course of Type 1 diabetes among Nepalese children aiming for the result thus obtained will help in proposing strategies for future management planning and resource allocation. Method: A longitudinal study of children with Type1 Diabetes Mellitus (T1DM) presented to pediatric endocrinology unit of Kanti Children’s Hospital (KCH) over the period of ten years (January 2013 to Dec 2023) was conducted. The data were retrieved retrospectively from patient’s record file, OPD record book, and the diabetic logbook of each patient regarding the basic demographic profile, clinical presentations, complications, investigations and course of disease. As per need interviewing was done to get further information and clarification. Data were entered into MS Excel and analyzed using SPSS version 26. Result: Among one hundred eighty-five children with T1DM enrolled in study 104 (56.2%) were male and 81 (43.8%) were female with M:F ratio of 1.27:1. The mean age of the patients was 9.5±4.1 years. More than two thirds (73.6%) were between the age of 5 to 14 years at the time of diagnosis. In terms of BMI, 123 (66.5%) were within the normal range, 41 (22.2%) were underweight, and 5 each (2.7%) were overweight and obese. The presenting complaints at the time of diagnosis were polyuria (93.5%), polydipsia (89.2%), weight loss (82.2%), polyphagia (69.2%) and weakness (67.6%). Presentation with diabetic ketoacidosis (DKA) and infection at the time of diagnosis was found in 54.1% and 18.9% children respectively. Conclusion: Most common clinical presentation of T1DM were typical osmotic features like polyuria, polydipsia and complications like DKA. The most common age of presentation was 5 to 14 years.